FACTORS AFFECTING THE INTERESTS OF ACCOUNTING STUDENTS STUDY PROGRAM SELECTION CAREER PUBLIC ACCOUNTANTS - Adi Irawan Setianto; Yusri Ahmad Harahap (Pusat P2M Politeknik Negeri Batam, 2017)
This study aims to examine the factors that affect the interests of students of accounting for choosing their public accounting careers. This research was conducted specifically on that polytechnic colleges and universities Batam, Riau Archipelago. The data collection is done by using a questionnaire to the respondent. This study tested the validity and reliability test, classic assumption test and multiple regression analysis test. This study is the financial reward positive and significant impact on student interest in choosing a public accountant, professional training positive and significant impact on student interest in choosing a public accountant, professional recognition positive and significant impact on student interest in choosing public accountants, social values ​​influence positive and significant impact on student interest in choosing a public accountant, the working environment positive and significant impact on student interest in choosing a public accountant, consideration of labor market positive and significant impact on student interest in choosing a public accounting, and personnel positive and significant impact on student interest in choose a public accountant. Limitations of the study is a special student majoring in accounting. As for the implications and suggestions for future research is the sample size was increased to enable obtain more accurate data, add another variable or using references other variables that influence the selection of career public accountant.